Learning Outcomes of Mandarin Language Education Program Study Universitas Negeri Semarang Graduates: Alignment with Educational Workforce Needs - Anggraeni, Anggraeni; Supriatnaningsih, Rina; Pamuji, Dian Yuni; Wei-Te, Liu (Asosiasi Program Studi Mandarin Indonesia, 2024)
Abstract: The Universitas Negeri Semarang (UNNES) Mandarin Language Education Program Study is designed to train graduates for educator careers. However, it also responds to the significant need for graduates proficient in Mandarin within the industrial field. This response is further shaped by the new curriculum policy established by the Indonesian Minister of Education, which mandates that students must be prepared to enter the workforce before graduation. The Mandarin Language Education Program Study at UNNES is adaptable and responsive, developing learning outcomes that correspond with the requirements of the educational workforce. This study aims to describe learning outcomes, focusing on attitude, general skills, special skills, and knowledge for educational workforce needs. The research methodology employed is a robust and reliable descriptive qualitative approach, which includes practical data sources such as alumni, stakeholders, and job vacancy information. The results were derived from analyzing questionnaire responses from alumni employed in the education sector, stakeholders, and job vacancy data from Jobstreet.com. The data is processed according to the results of the four criteria for learning outcomes.Keywords: Learning Outcomes; Graduate; Mandarin Language Education Program Study UNNES; Educational Workforce NeedsAbstract: Program Studi Pendidikan Bahasa Mandarin Universitas Negeri Semarang (UNNES) dirancang untuk menyiapkan lulusan untuk berkarir sebagai pendidik. Namun, program studi ini juga memenuhi kebutuhan yang sangat banyak akan lulusan yang mahir berbahasa Mandarin di dunia industri. Hal ini semakin didukung oleh kebijakan kurikulum baru yang ditetapkan oleh Menteri Pendidikan Indonesia, yang menyatakan bahwa siswa harus siap memasuki dunia kerja sebelum lulus. Program Studi Pendidikan Bahasa Mandarin UNNES bersifat adaptif dan responsif, mengembangkan capaian pembelajaran yang sesuai dengan kebutuhan tenaga kependidikan. Penelitian ini bertujuan untuk mendeskripsikan capaian pembelajaran, berfokus pada sikap, keterampilan umum, keterampilan khusus, dan pengetahuan untuk kebutuhan tenaga kependidikan. Metodologi penelitian yang digunakan adalah pendekatan kualitatif deskriptif yang kuat dan andal. Sumber data meliputi alumni, pemangku kepentingan, dan informasi lowongan kerja. Hasil penelitian diperoleh dari analisis respons kuesioner dari alumni yang bekerja di sektor pendidikan, pemangku kepentingan, dan data lowongan kerja dari Jobstreet.com. Data diolah sesuai dengan hasil dari empat kriteria capaian pembelajaran.Keywords: Capaian Pembelajaran Lulusan; Alumni; Prodi Pendidikan Bahasa Mandarin UNNES; Kebutuhan Tenaga Kependidikan.